Analysis of IT Performance on Management HR of Equity Firm Using COBIT 5 - Mochammad Herdin Adi Syahputra; Rudi Sutomo (Universitas Bina Darma, 2023)
An Indonesian equity company is involved in project management for the construction of mechanical systems and the development of electrical and chemical waste treatment systems. With a strong emphasis on continuous improvement and customer satisfaction, the company is dedicated to enhancing its services. However, additional human resources are needed, particularly in the IT field, to align with the business objectives that have not yet been achieved. Despite establishing a minimum requirement of ten years of work experience, the study employs the COBIT 5 framework to evaluate the competency levels in IT governance. The analysis reveals four crucial domains: APO01 (Managing the IT Management Framework), APO07 (Human Resource Management), APO12 (Assessing and Managing Risks), and EDM04 (Ensuring Resource Optimization). It is evident that both EDM04 and APO01 are currently at level 1 and have not reached the desired level. Furthermore, APO07 and APO12 are at level 2 and still need to progress towards their ideal targets. Although Human Resource Management has performed satisfactorily, there is room for improvement in the upcoming year to further enhance its performance.